2005
DOI: 10.1089/bsp.2005.3.31
|View full text |Cite
|
Sign up to set email alerts
|

Are Public Health Workers Aware of What They Don't Know?

Abstract: The modest sizes of the correlations suggest that workers are weak judges of what they know and do not know. To prepare public workers for emergency events, it is suggested that two steps are important: (1) using the core competencies, develop a local response plan, and (2) develop an objective knowledge test to assess workers' knowledge of the local response plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…5 The post-9/11 literature is replete with information regarding preparedness and the pivotal role played by the public health workforce. [6][7][8][9][10][11][12][13][14] Likewise, experienced public health practitioners have offered their thoughtful approaches for overall public health agency preparedness, particularly in conjunction with critical system partners. [15][16][17][18][19][20][21] In addition, innovative assessment tools have been developed to assist state and local health departments in determining the community's overall level of readiness.…”
mentioning
confidence: 99%
“…5 The post-9/11 literature is replete with information regarding preparedness and the pivotal role played by the public health workforce. [6][7][8][9][10][11][12][13][14] Likewise, experienced public health practitioners have offered their thoughtful approaches for overall public health agency preparedness, particularly in conjunction with critical system partners. [15][16][17][18][19][20][21] In addition, innovative assessment tools have been developed to assist state and local health departments in determining the community's overall level of readiness.…”
mentioning
confidence: 99%
“…The handoff 4 has had the lowest mean score of satisfaction. It meets the assumption of Kerby et al (2005): a system with adequate resources does not ensure, by itself, a properly functioning system, without certain threshold of connectivity. Note that, in Figure 2, most of the relationships among the actors are asymmetric; the actors are Correlations among actor information centrality (AIC) and others centrality measures (p = 0,000) Centrality measure AIC/Handoff 1 AIC/Handoff 2 AIC/Handoff 3 AIC/Handoff 4 AIC/Handoff 5 AIC/Handoff 6 AIC/Handoff 7 Degree 0,93 0,94 0,94 0,87 0,93 0,95 0,98 Closeness 0,93 1,00 0,97 0,88 0,98 0,91 0,93 Betweenness 0,60* 0,94 0,87 0,65** 0,76** 0,77** 0,76** Eigenvector 0,98 1,00 0,70* 0,95 0,99 0,91 0,99 * p = 0,02 ** p = 0,01 positioned more on the periphery of the network and express low connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is useful to describe the integration and coordination of activities in public health, among other areas. Even if a system has adequate resources in terms of technology, training and funding, such components do not ensure alone a properly functioning system, without certain threshold of connectivity (Kerby et al, 2005).…”
Section: Centrality Measures In Social Networking Analysismentioning
confidence: 99%
“…"[3] The concept has been described as useful for describing the integration and coordination of the public health and emergency management network[3]. It has been reported that even if a system has ample resources in terms of equipment, training, and funding, these components will not function optimally if the system does not reach a threshold level of connectivity[4]. If, however, organizations have developed strong and mutual relationships, research suggests that the system as a whole will likely manage the crisis more efficiently and have greater capacity to adapt and improvise should an unexpected event outside of the specific action and contingency plans occur[3,4].…”
Section: Introductionmentioning
confidence: 99%